Integrating Total Quality Management with Strategic, Operational, and Human Resource Management: A Qualitative Exploration of Synergies for Enhanced Organizational Performance - Syamsul Alam; Edy Jumady; Yana Fajriah; Ardiansyah Halim; Sukarno Hatta (Manunggal Halim Jaya, 2024)
This research explores the integration of Total Quality Management (TQM) with strategic, operational, and human resource management practices. Employing a qualitative approach, it conducts a systematic review and synthesis of existing literature to understand this integration and its implications for organizational performance comprehensively. The research design thoroughly examines scholarly literature using academic databases and inclusion criteria to select relevant studies. Data analysis employs thematic analysis to identify recurring themes, patterns, and relationships across the literature. Findings reveal the significance of strategic alignment in maximizing the effectiveness of TQM initiatives, driving operational efficiency, and fostering employee engagement. Challenges such as resistance to change, cultural barriers, and resource constraints are also identified, underscoring the complexity of TQM integration. The research highlights the need for theoretical advancements and managerial practices to overcome challenges and leverage opportunities for achieving sustainable competitive advantage. The integration of TQM with strategic, operational, and human resource management practices offers organizations a holistic approach to enhance organizational performance and achieve excellence in quality management.